2010
DOI: 10.3928/00220124-20100224-05
|View full text |Cite
|
Sign up to set email alerts
|

Does Increasing Education Increase the Probability of Promotion? The Case of Registered Nurses in Canada

Abstract: Little research has examined the effect of education on promotional opportunities for nurses. This article adds to the literature by addressing this question. This study uses data from the confidential master files from the 2001 Canadian Census on Individuals. The results of this study show that there is an increased probability of promotion to supervisory positions for registered nurses with a bachelor's degree. For both the male and female samples it was found that having a bachelor of nursing certification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…RN education might affect the job opportunities of RNs, specifically the job titles they may have. For example, baccalaureate RNs have been shown to be more likely to be promoted into managerial positions (Spetz ; Buhr ). We do not control for job title in the wage equations, because if it is included the wage change associated with holding higher paying nursing positions would be explained by the coefficient(s) of the job title variable(s).…”
Section: Methodsmentioning
confidence: 99%
“…RN education might affect the job opportunities of RNs, specifically the job titles they may have. For example, baccalaureate RNs have been shown to be more likely to be promoted into managerial positions (Spetz ; Buhr ). We do not control for job title in the wage equations, because if it is included the wage change associated with holding higher paying nursing positions would be explained by the coefficient(s) of the job title variable(s).…”
Section: Methodsmentioning
confidence: 99%
“…A study of Canadian nurses found that a higher level of education increased promotions to nurse supervisory positions. 11 Higher education can provide opportunities to work in less physically demanding roles such as administrators, educators, researchers, and so on. These roles are certainly mentally challenging, but are usually not as physically demanding as what's required in direct patient care.…”
Section: Higher Learningmentioning
confidence: 99%
“…The study was based on the theory of human capital, in which training and competencies improve productivity in one's profession (Buhr, ). As initially proposed by economists, human capital can be general or specific (Becker, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%